Investigasi Peran Kepemimpinan Transformasional Dalam Meningkatkan Kinerja Karyawan Melalui Peran Motivasi Intrinsik di PT. Adi Satria Abadi Bantul - Rizka Nur Fitriani (EBBANK, 2020)
The purpose of this study was to describe (1) The Effect of Transformational Leadership on Employee Performance through the Motivation Role of Intrinsik at PT. Adi Satria Abadi Bantul. (2) Effect of Transformational Leadership on Employee Performance at PT. Adi Satria Abadi Bantul. (3) The Influence of Technique Motivation on Employee Performance at PT. Adi Satria Abadi Bantul.The population in this study were all employees of PT. Adi Satria Abadi Bantul, amounting to 300 employees with a sample of 75 employees. This research uses accidental sampling technique, which is the selection of samples that happen to be found by researchers. Analysis of the data used is linear regression.The results showed that (1) Transformational Leadership had a significant positive effect on Employee Performance through Intrinsic Motivation (2) Transformational Leadership had a significant positive effect on Employee Performance. (3) Intrinsic Motivation has a significant positive effect on Employee Performance.